Bangladesh Experience of Radiofrequency Ablation for Management of Hepatic Haemangioma - Noor E Alam, Sheikh Mohammad; Akbar, Sheikh Mohammad Fazle; Mahtab, Musarrat; Lima, Taslima Akter; Das, Nirupoma; Nasir, Nadia Binte; Shahriar, Nasif; Abdur Rahman, Md.; Sadman, Omar Faruque; Abdur Rahim, Md.; Moben, Ahmed Lutful; Begum, Rokshana; et al. (British Journal of Healthcare and Medical Research, 2025)
Introduction: Hepatic haemangiomas are most common benign tumors of the liver. These are vascular malformations, which are usually asymptomatic. However, these may be potential cause of life-threatening complications at times. Methods: There are several treatment options for hepatic haemangiomas. Here we discuss radiofrequency ablation for management of this condition. Results: We included 15 patients with hepatic haemangiomas in this single arm, single Centre study. We ablated their haemangiomas with radiofrequency ablation. None had any major adverse event. At 6-month follow-up, the size of hepatic haemangioma was reduced in all patients. Conclusion: The study suggests radiofrequency ablation for management of hepatic haemangiomas is safe and effective.